2009
DOI: 10.1074/jbc.m109.042127
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Caveolin-1 Coordinate Interleukin-1β (IL-1β)-dependent Activation of NFκB by Controlling Endocytosis of Nox2 and IL-1β Receptor 1 from the Plasma Membrane

Abstract: Recent evidence suggests that signaling by the proinflammatory cytokine interleukin-1␤ (IL-1␤) is dependent on reactive oxygen species derived from NADPH oxidase. Redox signaling in response to IL-1␤ is known to require endocytosis of its cognate receptor (IL-1R1) following ligand binding and the formation of redox-active signaling endosomes that contain Nox2 (also called redoxosomes). The consequent generation of reactive oxygen species by redoxosomes is responsible for the downstream recruitment of IL-1R1 ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 55 publications
5
94
0
Order By: Relevance
“…Lipid rafts have also been reported to be essential for NF-kB activation induced by a diverse set of stimuli, such as interleukin (IL)-1b, CD40L, and lipopolysaccharides (LPS; refs. 8,9,12). Collectively, these findings indicate that lipid rafts play important roles in the activation of proximal NF-kB signaling.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Lipid rafts have also been reported to be essential for NF-kB activation induced by a diverse set of stimuli, such as interleukin (IL)-1b, CD40L, and lipopolysaccharides (LPS; refs. 8,9,12). Collectively, these findings indicate that lipid rafts play important roles in the activation of proximal NF-kB signaling.…”
Section: Introductionmentioning
confidence: 69%
“…Functioning as a physical platform, lipid rafts have been reported to be essential for NF-kB signaling transduction via inducing signaling molecules in close proximity (7)(8)(9)(10)(11). In response to TNF-a, TNF receptor (TNFR) translocates to lipid rafts and forms a signaling complex through association with the adaptor proteins, TRADD, TRAF2, and RIP1.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of RbohC in the plasma membrane requires vesicle trafficking and phagocyte NADPH oxidase can be internalized from the plasma membrane by endocytosis (Takeda et al, 2008;Oakley et al, 2009). However, whether the localization of RbohD requires endocytosis and the contribution of the different endocytic pathways remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts have been shown to serve as signalling platforms in a variety of cell types (most notably B-cells) (Dykstra et al, 2003;Dykstra et al, 2001;Harder and Engelhardt, 2004;Simons and Toomre, 2000) and have been implicated in NF-kB signalling (e.g. Oakley et al, 2009;Waterfield et al, 2010), so any stabilisation of lipid rafts would stabilise these signalling platforms and thereby extend the longevity of any downstream signalling, thereby activating NFkB dependent pathways. We initially confirmed that expression of tetherin leads to an activation of the NF-kB pathway (Fig.…”
Section: Nf-kb Activation Following Tetherin Expressionmentioning
confidence: 99%